The Three Pigs: Can They Blow Us Into Critical Media Literacy Old School Style?. Issue 3 (2nd July 2016) - Flores-Koulish, Stephanie A.; Smith-D'Arezzo, Wendy Marie
ABSTRACT: In this article, the authors show how groups of 2nd- and 4th-grade students in an urban school district responded to a postmodern children's book, The Three Pigs by David Wiesner (2001). The students came to the project from basal-based direct instruction, and here they were offered a more constructivist opportunity to engage with a text. The authors found that this text afforded the students with opportunities for discussion and thus were able to hone critical literacy skills, which correspond with critical media literacy concepts and new expectations within the Common Core State Standards (CCSS). The authors also make the case that these texts can be especially useful in settings still lacking sophisticated technologies. Thus, students can still gain complex literacy concepts despite a school's limited resources. What they find then is that students gain conceptual depth from postmodern children's literature using constructivist teaching methods.